2018
DOI: 10.12973/iji.2018.11226a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Flipped Classroom Model on Students’ Classroom Engagement in Teaching English

Abstract: In the current study, the aim is to determine the effect of flipped classroom model on students' classroom engagement in teaching English. This research was conducted within the English course for four weeks period in the Spring term in 2016-2017 school year in a secondary school in the city of Hatay. In the study, pretest/post-test quasi-experimental design with control group was applied. The experimental group was lectured with flipped classroom model whereas the courses were carried out based on the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 17 publications
(14 reference statements)
3
87
0
12
Order By: Relevance
“…This theme of active learning experiences showed that almost all participants in this study acknowledged that applying flipped online course in learning English was more effective as compared to the traditional classroom. The finding of this study was supported by research done by Ayçiçek and Yanpar (2018) and Zappe, Leicht, Messner, Litzinger and Lee (2009) that mentioned an active learning environment tends to make the students actively involved in a discussion and problem-solving. Zhiru, Kui and Lynley (2018), Chung, Chi and Khe (2018) and Overmyer (2012) also believed that in the FC, students are more confident and active in classroom activities because they have prepared to learn material outside of the class.…”
Section: Discussionsupporting
confidence: 81%
“…This theme of active learning experiences showed that almost all participants in this study acknowledged that applying flipped online course in learning English was more effective as compared to the traditional classroom. The finding of this study was supported by research done by Ayçiçek and Yanpar (2018) and Zappe, Leicht, Messner, Litzinger and Lee (2009) that mentioned an active learning environment tends to make the students actively involved in a discussion and problem-solving. Zhiru, Kui and Lynley (2018), Chung, Chi and Khe (2018) and Overmyer (2012) also believed that in the FC, students are more confident and active in classroom activities because they have prepared to learn material outside of the class.…”
Section: Discussionsupporting
confidence: 81%
“…The important concept of the flipped learning approach stems from constructivist learning theory that underlying of learners' role in their learning. This approach will assist them to become active learners while enhancing their engagement in classrooms Ayçiçek and Yanpar Yelken (2018). Nowadays, the flipped classroom technology approach has gained the attention of numerous researchers and educators (Basal, 2015;Ahmed, 2016;Sakulprasertsri, 2017).…”
Section: Introduction Of Flipped Classroom Technology Approachmentioning
confidence: 99%
“…The teacher is in the role of a mentor. He is taking care of students in individual and group work, being able to closely follow the learning processes of students with and without special needs related to learning, improving teacher-student-parent interaction, developing cooperative working skills and being able to follow students outside the classroom (Ayçiçek & Yanpar Yelken, 2018;Bergmann & Sams, 2012Cabi, 2018;Fulton, 2012;Herreid & Schiller, 2013;Karadeniz, 2015;LaFee, 2013;Prashar, 2015;Tütüncü & Aksu, 2018;Urfa, 2018). Some disadvantages such as requiring more effort and expertise in some aspects (preparing econtent and expertness in a subject), taking precautions for student participation and International Journal of Instruction, January2019 • Vol.12, No.1 follow-up, possible problems with technological equipment (deficiency, malfunction, cost etc.…”
Section: Literature Reviewmentioning
confidence: 99%